Permeation of intrinsic water into ethanol- and water-saturated, monomer-infiltrated dentin bond interfaces - Sartori, Neimar; Peruchi, Lais Dalmagro; Phark, Jin-Ho; Lopes, Maria M.; Araujo, Elito; Vieira, Luiz C. C.; Belli, Renan; Duarte, Silas (Dental Materials, 2015)
The aim of this study was to evaluate the formation of dentin bonding interfaces using the water-wet and the ethanol-wet techniques under simulated pulpal pressure, and to assess the effect of adhesive solvent and thermomechanical loading.Flat dentin surfaces were restored under 20mm-simulated pulpal pressure following two bonding approaches (water-wet and ethanol-wet bonding) in combination with dental adhesives containing ethanol (Single Bond Plus and Scotchbond Multi-Purpose) or acetone (One-Step Plus and All-Bond 2) as solvent. Half of the restorations of each subgroup were subjected to thermocycling followed by cyclic loading (three teeth per group). Bond strength was measured using the microtensile bond strength test and fitted to a Weibull distribution (?=0.05). Ultrastructural analyses of the interface and leakage/nanoleakage evaluation were performed using confocal scanning microscopy (CLSM) and transmission electron microscopy (TEM).Water permeation through dentin tubules during adhesive application prevented adequate penetration of adhesive monomers into the demineralized collagen matrix in both bonding techniques, but more severely for water-wet bonding. Acetone-solvated adhesives showed worse bonding performance and hybridization than ethanol-based systems when applied in the ethanol-wet mode, both before and after thermomechanical challenge.The ethanol-wet bonding technique helps to compensate for water permeation from dentin tubules during the bonding procedures to form more stable dentin bonds, especially when used in conjunction to ethanol-solvated systems.
EVALuna2:24675